Learning Istima’ Based on Ibnu Tufail's Humanism Approach at Applied Islamic School Prof. Muhajrin Palembang - Rendi Sabana; Zaini, Hisyam; Nurcholis, Agung; Mark Daniel , Shockley; Hidayah, Nurul (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study aims to investigate the application of Ibn Tufail’s humanistic approach in teaching listening (istima’) skills in Arabic language learning, focusing on its potential to enhance comprehension through active student engagement. Listening skills are fundamental to understanding Arabic; however, many teaching methods remain technical and mechanical, often overlooking critical thinking and reflection. Ibn Tufail, a 12th-century Muslim philosopher, emphasizes learning through direct experience and intellectual freedom, encouraging learners to relate auditory input to their personal experiences. This qualitative study explores students’ and teachers’ perspectives, experiences, and perceptions of istima’ instruction and the humanistic approach at Prof. Muhajirin Applied Islamic School in Palembang. Data were collected through in-depth interviews, classroom observations, and focus group discussions. The findings reveal that applying Ibn Tufail’s principles fosters active student participation and the development of teaching content that connects listening materials with learners’ experiences, ultimately enhancing the quality of Arabic language education.